2012
DOI: 10.1152/ajprenal.00380.2011
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase inhibition prevents proteinuria in immune-complex-mediated antipodocyte nephritis

Abstract: TN. Rho-kinase inhibition prevents proteinuria in immune-complex-mediated antipodocyte nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…In the present study, MPGN podocytes showed not only morphological changes but also abnormalities in SD protein localization; nephrin, podocin, and synaptopodin were localized to the cell body as well as FP, showing a granular pattern. More recent studies indicated that Rho-kinases play a pivotal role in the organization of the actin cytoskeleton of podocytes [38,39,40]. Asanuma et al [39] suggested that Rho-kinase regulates actin-myosin-containing stress fibers in the podocyte cell body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, MPGN podocytes showed not only morphological changes but also abnormalities in SD protein localization; nephrin, podocin, and synaptopodin were localized to the cell body as well as FP, showing a granular pattern. More recent studies indicated that Rho-kinases play a pivotal role in the organization of the actin cytoskeleton of podocytes [38,39,40]. Asanuma et al [39] suggested that Rho-kinase regulates actin-myosin-containing stress fibers in the podocyte cell body.…”
Section: Discussionmentioning
confidence: 99%
“…Asanuma et al [39] suggested that Rho-kinase regulates actin-myosin-containing stress fibers in the podocyte cell body. Meyer-Schwesinger et al [[40] demonstrated that increased activation of Rho-kinases leads to cytoskeletal rearrangement in the course of antibody-mediated podocyte injury, culminating in FP effacement, proteinuria, and detachment into the urine, and that this could be prevented by Rho-kinase inhibition. Furthermore, in vitro and in vivo studies have revealed that proinflammatory cytokines such as IL-1β and TNF-α are involved in Rho-kinase pathway activation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Lysates from the stimulated cells were assessed by western blot analysis using murine anti-UCH-L1 antibody, and β-actin was used as a control for protein loading. Murine podocytes were pre-treated with PDTC at the stated concentrations for 2 h, following stimulation with (A) TNF-α ( via the immune injury mechanism (1,2,25,32,33). Studies have demonstrated that the changes to podocyte morphology and function following injury were closely associated with the abnormalities of numerous podocyte proteins, including UCH-L1, nephrin and synaptopondin (1,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of RhoA in podocytes induces FSGS [ 20 ] with disruption of the actin cytoskeleton [ 21 ]. Rho-kinase inhibition protected podocytes and reduced proteinuria in one mouse model [ 22 ]. There is still some controversy about which protein forms the most logical target, with another recent paper suggesting that RhoA is not the key member of the family in podocytes, instead providing evidence that another Rho family GTPase, cdc42, is the key one for maintenance of the podocyte actin cytoskeleton [ 23 ].…”
Section: What About Novel More Specific Forms Of Therapy?mentioning
confidence: 99%